2002
DOI: 10.1007/s10198-002-0104-y
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology, economics and quality of life burden of age-related macular degeneration in France, Germany, Italy and the United Kingdom

Abstract: Age-related macular degeneration (AMD) is a major public health issue, but little is known about the economics of the disease. This contribution describes the epidemiology and the economics of AMD in four European countries: France, Germany, Italy and the United Kingdom (UK). We reviewed published information on AMD, including guidelines, official statistics, and local literature and interviewed AMD experts. All available health-related quality of life studies (HRQoL) on AMD were also reviewed. Data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 36 publications
0
24
0
1
Order By: Relevance
“…Bonastre et al [19] recently estimated the total burden of AMD in four European countries, including Italy, using secondary data on resource utilization of various treatments for AMD, derived mainly from the literature and from expert opinions.This study reported the cost of the main treatment options for AMD patients with CNV, i.e., laser photocoagulation and PDT. The average typical number of each procedure was based on experts' estimates, and the unit costs were INHS tariffs (Decreto Ministeriale "Prestazioni di assistenza specialistica ambulatoriale erogabili nell'ambito del Servizio Sanitario Nazionale e relative tariffe," 22 July 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Bonastre et al [19] recently estimated the total burden of AMD in four European countries, including Italy, using secondary data on resource utilization of various treatments for AMD, derived mainly from the literature and from expert opinions.This study reported the cost of the main treatment options for AMD patients with CNV, i.e., laser photocoagulation and PDT. The average typical number of each procedure was based on experts' estimates, and the unit costs were INHS tariffs (Decreto Ministeriale "Prestazioni di assistenza specialistica ambulatoriale erogabili nell'ambito del Servizio Sanitario Nazionale e relative tariffe," 22 July 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For the individual, severe visual loss from AMD is equivalent in terms of reduction in quality of life to having severe prostatic cancer with uncontrollable pain (Brown et al 2005). For the nation, the economic burden to the United Kingdom of AMD has been estimated to be as much as 101.1 million Euros (Bonastre et al 2002). AMD has been judged on the basis of a spectrum of measures of patient disability to be the third most disabling disease in the US population after diabetes and cancer (SST 2004;Brody et al 2001;Rovner et al 2002;Royal College of Ophthalmologists 2002).…”
Section: Introductionmentioning
confidence: 99%
“…7 The loss of central vision in patients afflicted with AMD has a dramatic and adverse impact on their quality of life. 8 For example, the impact of vision loss associated with AMD may result in an inability to drive, to read, to recognize faces, or to watch television, with a consequential loss of social independence and increasing need for family support, 9 which is a major concern in the context of an advancing population. The financial burden of vision loss and/or impairment may be classed as direct or indirect.…”
Section: Introductionmentioning
confidence: 99%